Direct oral anticoagulants versus vitamin K antagonists in epistaxis patients: A systematic review and meta‐analysis. (2nd December 2021) - Stanković, Petar; Hoch, Stephan; Rudhart, Stefan; Obradović, Danilo; Dagres, Nikolaos; Wilhelm, Thomas
Abstract: Objective: Epistaxis is the most common otolaryngological emergency and up to one third of patients in treated on an inpatient basis take oral anticoagulants (OAC). Direct oral anticoagulants (DOAC), an OAC subgroup, have been on the market since 2010 and are being increasingly prescribed due to the cardiological and haematological guidelines that favour them over vitamin K antagonists (VKA), the older of the OAC subgroups. The present study aims to investigate which subgroup of epistaxis patients taking OACs has a more favourable outcome. Design/setting: A systematic review and meta‐analysis were performed according to the PRISMA 2020 statement using the PubMed and Cochrane Library databases. Continuous data were analysed and standardised mean difference (SMD) was calculated according to Hedges' g. Dichotomous data were analysed, and the Mantel‐Haenszel method was applied to establish the odds ratio (OR). Heterogeneity was assessed according to the I 2  statistics. Main outcome/results: A total of eight reports covering 1390 patients were included in the final synthesis. The pooled analysis demonstrated significantly shorter hospital stays in the DOAC group (SMD = −0.22, 95% CI−0.42 to −0.02, p  = .03) and a significantly higher rate of posterior bleeding in the VKA group (OR = .39, 95% CI 0.23 to 0.68, p  = .001). No statistically significant differences with regard to recurrence rates, admission rates, the need for transfusion or surgical intervention ( p  = .57, .12, .57 and .38 respectively) were found. Conclusion: According to this meta‐analysis, epistaxis patients taking DOACs have a more favourable outcome than patients taking VKAs.